Can I please see an example of this? Also how do you factor -3x^2 +10x -3?
-3x^2 +10x -3
= -(3x^2 -10x +3)
= -(3x-1)(x-3) <==Answer
Ideas: Take "-" sign out first.
Can I please see an example of this? Also how do you factor -3x^2 +10x -3?
-3x^2 +10x -3
= -(3x^2 -10x +3)
= -(3x-1)(x-3) <==Answer
Ideas: Take "-" sign out first.
Any trinomial of the type ax^{2}+bx+c can be factored as follows: a*(x-x_{1})*(x-x_{2}), where x_{1} and x_{2} are the roots of quadratic equation ax^{2}+bx+c=0;
So, in your case, -3x^{2}+10x-3 can be factored as follows:
1) Let us solve -3x^{2}+10x-3=0;
Quadratic formula gives us: x_{1,2}={-10±√[10^{2}-4*(-3)*(-3)]}/(2*(-3))=(-10±√64)/-6;
x_{1}=3; x_{2}=1/3;
2) Let us write the factorization:
-3x^{2}+10x-3=(-3)*(x-3)*(x-1/3) ;
Factor (-3) can be distributed into the second parentheses to obtain more compact expression:
-3x^{2}+10x-3=(x-3)*(1-3x)